THE EFFECT OF OPERATIONS ON THERMAL COMFORT AT THE MAAIMMASKUB MOSQUE, BANDUNG - Nurjaman, Tatang; Syahriyah, Dewi Rachmaniatus (Ide dan Dialog Desain Indonesia (Idealog), 2023)
The mosque is a place of worship for Muslims and is also a place to establish friendship with fellow Muslims. Comfort and comfort in worshiping in the mosque must remain a priority. Therefore, the aimof this research is to determine the ef ect of air openings and other thermal comfort elements on thermal comfort both in worship and during interpersonal sessions at the Maaimmaskub Mosque, Bandung. Themethod that will be used in this research is a quantitative descriptive method by conducting surveys andexperimental observations at the Maaimmaskub Mosque in Bandung. The research results obtained show that the openings in the mihrab area are elements that have a positive influence on air circulation and room humidity so that they can support the thermal comfort of the Maaimmaskub Mosque. The pool element in the mihrab area also contributes to air humidity in the prayer room of the Maaimmaskub Mosque. The building elevation element influences the speed of air passing through the openings in the mihrab area, doors and windows. The prayer room at the Maaimmaskub Mosque which is the object of research meets thermal comfort with an optimal comfortable sensation from the average ef ective temperature (TE). Keywords : Air Openings, Thermal Comfort, Maaimmaskub Mosque